First reported cases of linezolid-resistant vancomycin-resistant enterococci in South-East Asia: A report of three cases and literature review - Wei Chuan Chua (SAGE Publishing, 2021)
Infections with vancomycin-resistant enterococci (VRE) have limited treatment options, with linezolid the mainstay of therapy. The emergence of linezolid-resistant vancomycin-resistant enterococci (LRVRE) further restricts the therapeutic options. LRVRE isolated from clinical specimen have not previously been reported in South-East Asia. Here, we report three clinical cases of LRVRE from a teaching hospital in Malaysia. Three isolates of Enterococcus faecium were isolated from three different patients. These isolates were determined to be resistant to both vancomycin and linezolid by Etest gradient diffusion test and Vitek2 automated antibiotic susceptibility testing, respectively. Retrospective analysis of the microbiological and clinical data of the three patients was undertaken. LRVRE were isolated from from tissue and peritoneal fluid of two patients who underwent complicated abdominal surgery. Another patient with underlying acute lymphoblastic leukaemia developed neutropenia following chemotherapy. LRVRE were isolated from the blood culture. All three patients were not treated with linezolid. The possible risk factors for LRVRE acquisition are administration of multiple broad-spectrum antimicrobials and disruption of the gastrointestinal mucosa. The appearance of LRVRE in increasingly widespread geographic locations may lead to a global health threat. Judicious use of broad-spectrum antimicrobials and infection-control practices are crucial to curb its spread.